1978
DOI: 10.1073/pnas.75.3.1353
|View full text |Cite
|
Sign up to set email alerts
|

Colony size distributions as a measure of in vivo and in vitro aging.

Abstract: Recently it has been demonstrated that cell cultures from older human subjects, even during their first few in vitro passages, exhibit diminished replicative ability when compared to parallel cultures derived from young subjects (5). However, these studies have examined the replicative behavior of cell populations. Because human diploid cell cultures are heterogeneous in nature, it is also vital to examine the proliferative behavior of human cells as a function of aging at the level of the individual cell Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
1
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(82 citation statements)
references
References 13 publications
8
72
1
1
Order By: Relevance
“…A similar difference was also reported in a comparison of cultures from young (21-36 years) and old (63-92 years) donors (Schneider and Mitsui 1976). A further correlation between in vitro and in vivo ageing was found by Smith et al (1978) in studies on age-related changes in colony size distributions among individual fibroblasts.…”
Section: Do Somatic Cells Really Age?supporting
confidence: 81%
“…A similar difference was also reported in a comparison of cultures from young (21-36 years) and old (63-92 years) donors (Schneider and Mitsui 1976). A further correlation between in vitro and in vivo ageing was found by Smith et al (1978) in studies on age-related changes in colony size distributions among individual fibroblasts.…”
Section: Do Somatic Cells Really Age?supporting
confidence: 81%
“…Passaged cultures proceeded through the same stages; however, the rate of growth in the log phase and the final number of cells after a fixed period in culture gradually diminished as a function of continued passaging. This decrease in the rate of growth, as well as the total number of cells as a function of increasing passage number, could be attributed to a small population of cells in each passage developing the broad, flattened morphology characteristic of cells entering G 0 , thus resulting in a smaller number of actively dividing cells remaining in the population [14,30,34]. Therefore, loss of doubling potential was accelerated in the DMEM-F12K cultures by the onset of cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Some cells appeared to begin dividing immediately upon migration from the bone fragment, and others failed to yield colonies at all or did so only after several days in culture. Previous studies have shown that fibroblasts, which are capable of quickly adhering and establishing rapidly growing colonies, undergo an increased number of total population doublings as compared with cells that slowly divide and form smaller colonies [30]. Our data support previous research into the aging characteristics of bone marrow stromal cells, where the confirmed presence of two types of adherent cells in primary culture, a rapidly dividing spindleshaped cell type and a much slower dividing broad and flattened cell type, was observed [14,31].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has also been shown that a large proportion of cells in a mass culture possess very limited proliferative capacity (32) and that the maximum MPD of clones which make up the mass culture are bimodally distributed (31, 33). Thus, one subpopulation of clones has low replicative potential whereas the other reaches the higher maximum MPD approximately equal to that of the mass culture.…”
Section: -He Clonat Selection Hypothesismentioning
confidence: 99%
“…2). Three clones (13,26,32) were assayed only at one stage. Of the remaining clones, two groups could be identified: group A, comprising seven clones (2,10,13,18,29,30,36), in which the error frequency remained relatively constant through subsequent passage although clones 10 and 29 were only assayed singly at two passage levels; group B, comprising two clones (8 and 14) in which an abrupt increase in error frequency at later passage was observed.…”
Section: Clonal Error Frequenciesmentioning
confidence: 99%